Frontispiece: Enantioselective Dihalogenation of Alkenes. Issue 14 (8th March 2021) - Bock, Jonathan; Guria, Sudip; Wedek, Volker; Hennecke, Ulrich
Abstract : Dihalogenation of alkenes is one of the classic reactions in organic chemistry and a prime example of an electrophilic addition reaction. Although being studied intensely, the development of reagent‐controlled, enantioselective dihalogenation is still challenging. Read more about current method development and mechanistic aspects in enantioselective dihalogenation in the Minireview by U. Hennecke et al. on page 4517 .